2013
DOI: 10.1007/s10072-013-1340-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of thromboxane A2 receptor gene polymorphisms with cerebral infarction in a Chinese population

Abstract: Platelet aggregation is crucial for the development of cerebral infarction (CI) and it is markedly increased due to the binding of thromboxane A2 (TXA2) to its receptor (TXA2R). Therefore, TXA2R plays a central role in the pathogenesis of atherosclerosis and thrombosis. This study aimed to investigate the relationship between human TXA2R gene single nucleotide polymorphisms (SNPs) and non-cardiogenic CI in a Chinese cohort. Two SNPs, rs768963 and rs4523, located in the regulatory and coding regions of TXA2R ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Maintaining homeostasis of PGI 2 /TXA 2 ratio can play an important role in regulating cerebral blood flow to respond with ischemia [25]. In contrast, the imbalance in PGI 2 and TXA 2 production is involved in the pathophysiology of myocardial infarction, atherosclerosis, and CI [23, 26, 27]. In recent years, more attentions have been focused on the functions of PGI 2 and TXA 2 in regulating blood coagulation and vascular constriction [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining homeostasis of PGI 2 /TXA 2 ratio can play an important role in regulating cerebral blood flow to respond with ischemia [25]. In contrast, the imbalance in PGI 2 and TXA 2 production is involved in the pathophysiology of myocardial infarction, atherosclerosis, and CI [23, 26, 27]. In recent years, more attentions have been focused on the functions of PGI 2 and TXA 2 in regulating blood coagulation and vascular constriction [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…The binding of TXA 2 to its specific receptor (TXA 2 receptor, encoded by TBXA2R) could induce platelet activation and aggregation [7] . When the COX-dependent pathway is strongly inhibited by aspirin, maximal aggregation will then require the platelet activators in the COX-independent pathway.…”
Section: Original Articlementioning
confidence: 99%
“…Zhao et al found that allele C of TXA2R rs768963 is associated with occurrence of ischemic stroke in this cohort; however, no significant association could be established between variants of rs4523 and ischemic stroke (Table 3 & 4) [38]. A positive relationship between C allele of rs768963 and stroke was earlier observed in a study on Japanese patients by Kaneko et al Interestingly, it was also demonstrated that frequency of C-T-C haplotype consisting of Table 5.…”
Section: Other Platelet's Receptorsmentioning
confidence: 80%
“…Thromboxane A2 upon binding to its specific receptor functions as a vasoconstrictor and promoter of platelet aggregation. Thus, it is directly involved in the development of thrombosis and atherosclerosis which, in turn, may impose a considerable risk of stroke [38]. The gene encoding TBXA2R is located on chromosome 19p13.3 and has five exons.…”
Section: Other Platelet's Receptorsmentioning
confidence: 99%